Focused Cardiac Ultrasound and the Periresuscitative Period: A Case Series of Resident-Performed Echocardiographic Assessment Using Subcostal-Only View in Advanced Life Support. Issue 10 (August 2020) - Bughrara, Nibras; Herrick, Susan L.; Leimer, Elizabeth; Sirigaddi, Krishnaveni; Roberts, Kevin; Pustavoitau, Aliaksei
Abstract : When incorporated into the 10-second pulse/rhythm check of the advanced life support (ALS) protocol, focused cardiac ultrasound is a useful adjunct to cardiopulmonary resuscitation. In this case series, we demonstrated the feasibility of echocardiographic assessment using subcostal-only view in ALS (EASy-ALS) performed by anesthesiology residents during the periresuscitative period after structured training. Residents obtained diagnostic quality images in 100% of the self-reported cases, which enabled them to identify cardiac motion and potentially reversible causes of hemodynamic instability. Implementation of EASy-ALS into practice requires system-wide changes in cardiac arrest management for consistency, quality, and further evaluation of patient outcomes. Abstract : Supplemental Digital Content is available in the text.